"Is Rhapsody in Blue in the Public Domain?": Copyright Knowledge of U.S. Music Librarians. (3rd April 2021) - Hunsaker, Amy J.; Schultz, Teresa Auch
ABSTRACT: Although several studies have looked at the perceived level of copyright knowledge among various types of librarians, none have looked at the actual copyright knowledge of U.S. music librarians. This project used a survey with two parts: The first asked music librarians about their perceived knowledge of copyright law, and the second included a copyright quiz of 13 questions. Seventy nine music librarians completed the entire survey, and results show no clear connection between perceived and actual knowledge of copyright. The results have implications for future training of music librarians in copyright issues.